EFFECT OF USING TEMPE WASTE AS A SUBSTITUTE OF CONCENTRATE AND COMPLETE RUMEN MODIFIER SUPPLEMENTATION ON CONSUMPTION AND DIGESTIBILITY OF DRY INGREDIENTS IN SHEEP FEED - Tarizareta, Britania Fitha; Suhartati, Fransisca Maria; Munasik, Munasik (ANGON: Journal of Animal Science and Technology, 2024)
Complete Rumen Modifier (CRM) is a feed supplement consisting of several components and mixtures that act as defamatory, methanogenesis inhibitors, bacterial growth factors, and triggers for fiber digestion. Feed supplements can be used to stimulate growth, prevent disease and improve the quality of rations. Tempe dregs and rice straws are wastes that can be used as ruminant animal feed, however, both are of low quality and high in crude fiber content. The high crude fiber affects the digestibility and consumption of feed, so it is necessary to treat it to improve the quality of the feed ingredients. Tempe dregs given to livestock are processed by drying beforehand while rice straw is treated chemically, namely by the ammonia method. This study aims to determine the effect of replacing Tempe dregs with concentrate and suplementation of CRM on the consumption and digestibility of dry matter for sheep feed. The material used were 18 rams aged 7-8 months. This research was carried out experimentally with the RAK analysis model as a group, namely the initial weight of sheep after feed adaptation in as many as 6 groups that served as replicates. The feed given to the sheep were concentrate in the control treatment (P1) and tempe dregs (P2 and P3) 2.5% of body weight. The treatments tested were P1: concentrate 2.5% of body weight (based on BK) + ammoniated rice straw (JPA) ad libitum, P2: dregs of tempe 2.5% of body weight (based on BK) + ammoniated rice straw (JPA) ad libitum, P3 : P2 + CRM 1%. The observed variables included consumption and dry matter digestibility of the feed. The results showed that replacing tempe dregs with concentrate and CRM supplementation had a very significant (P<0.01) effect on dry matter consumption and a significant effect (P<0.05) on feed dry matter digestibility. Based on the results of the study, it was shown that tempe dregs could completely replace concentrate because it could increase the consumption and feed dry matter digestibility for sheep feed without the need to add 1% CRM.